Perkembangan Aturan Peralihan Dari Kitab Undang-Undang Hukum Pidana Lama Ke Kitab Undang-Undang Hukum Pidana Nasional Baru Sebagai Wujud Pembaharuan - Daniel Hasudungan Nainggolan; Ade Adhari (UNES Law Review, 2023)
The enactment of Law Number 1 of 2023 on the Criminal Code marks a new era for criminal law in Indonesia. The New Criminal Code introduces fundamental changes in the penal system, observable through the formulation of criminal law norms in Book One General Provisions and Book Two Criminal Acts. One notable development is regarding the transitional provisions in Article 3 paragraphs (1)-(7) of the New Criminal Code. This article examines the evolution of transitional provisions from Article 1 paragraph (2) in the Old Criminal Code to Article 3 in the New Criminal Code. The research method employed in addressing this issue is doctrinal research, focusing on the Old and New Criminal Codes as primary legal sources and relying on literature reviews. The research findings indicate, firstly, that the transitional provisions in the Old Criminal Code are formulated in Article 1 paragraph (2). In this provision, the criteria used in the event of legal changes are those most favorable to the defendant. The formulation of these transitional provisions has weaknesses, including ambiguity in the meaning of legislative changes and determining what is most advantageous, among other things. Secondly, the transitional provisions in the New Criminal Code are formulated in Article 3, attempting to refine the provisions in the Old Criminal Code.